Ranked Choice Voting in Australia and America: Do Voters Follow Party Cues? - Benjamin Reilly (Politics and Governance, 2021)
Ranked choice voting (RCV) is experiencing a surge of interest in the United States, highlighted by its 2018 use for Congressional elections in Maine, the first application of a ranked ballot for national-level elections in American history. A century ago, the same system was introduced in another federal, two-party continental-sized democracy: Australia. RCV’s utility as a solution to inter-party coordination problems helps to explain its appeal in both countries, underscoring the potential benefits of a comparative analytical approach. This article examines this history of adoption and then turns to a comparison of recent RCV elections in Maine with state elections in New South Wales and Queensland, the two Australian states which share the same form of RCV as that used in the United States. This comparison shows how candidate and party endorsements influence voters’ rankings and can, over time, promote reciprocal exchanges between parties and broader systemic support for RCV. Such cross-partisan support helps explain the stability of RCV in Australia, with implications for the system’s prospects in the United States.